If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -4) + -1(2x + 4) = 20 Reorder the terms: 8(-4 + x) + -1(2x + 4) = 20 (-4 * 8 + x * 8) + -1(2x + 4) = 20 (-32 + 8x) + -1(2x + 4) = 20 Reorder the terms: -32 + 8x + -1(4 + 2x) = 20 -32 + 8x + (4 * -1 + 2x * -1) = 20 -32 + 8x + (-4 + -2x) = 20 Reorder the terms: -32 + -4 + 8x + -2x = 20 Combine like terms: -32 + -4 = -36 -36 + 8x + -2x = 20 Combine like terms: 8x + -2x = 6x -36 + 6x = 20 Solving -36 + 6x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 6x = 20 + 36 Combine like terms: -36 + 36 = 0 0 + 6x = 20 + 36 6x = 20 + 36 Combine like terms: 20 + 36 = 56 6x = 56 Divide each side by '6'. x = 9.333333333 Simplifying x = 9.333333333
| 2a-13=a | | 12xy+9xy= | | 2x(2)-5=-5 | | 8q-78=2q+66 | | X-3=2x+14 | | 1+5-2+8-5= | | 3x+7=-x-21 | | 5xsquared+45=0 | | 5+5-5= | | 2(3.14)16= | | 14j^2+91j+77=0 | | n^3t^2=nt^4 | | .25(3r-4)=.40 | | 0.57v=8.67 | | Y=-2x^2+3x-4 | | 2x+42l=x-24 | | 9z=10z-3 | | 4x-(3x+3)=2x-44 | | 8x+20-3x+3=x+28 | | 12x+3=25-2x | | (7+i)(3-4i)= | | 9w+3=w-9 | | 3x-8y=11fory | | 5.3x+2-4.1x=3.6x | | 2x+3x-100=5x | | -18k=-234 | | (3x)+(2x+26)=180 | | 5x+6y=20for | | -5n(5n-3)=0 | | -1+8x=-4x+5 | | 8x+5y=-105 | | 6t+3=8t+11 |